Post-traumatic Stress and Growth Among the Children and Adolescents in the Aftermath of COVID-19 - Bhushan, Braj; Basu, Sabnam; Ganai, Umer Jon (Frontiers in Psychology, 2022)
The Covid-19 pandemic has enkindled many mental health problems across the globe. Prominent among them is the prevalence of post-traumatic stress (PTS) with hosts of its precipitating factors being present in the surrounding. With India witnessing severe impact of the Covid-19 second wave, marked by a large number of hospitalizations, deaths, unemployment, imposition of lockdowns, etc., its repercussions on children and adolescent population demands particular attention. In this study we aim to examine the direct and the indirect exposure of Covid-19 related experiences on children and adolescents and its subsequent relationship with post-traumatic stress and post-traumatic growth (PTG). The direct exposure is operationalized in terms of death or hospitalization in the family while the indirect exposure was gauged in terms of exposure to media reports of Covid situation. Data from 412 children and adolescents in the age range of 9 to 20 years, revealed 68.9% of them with PTS. Interestingly, 39.8% of those reporting PTS were also experiencing PTG. Arousal appeared to be the most frequently reported characteristics of trauma. Multivariate analysis of variance (MANOVA) endorse significant difference between those with direct and indirect exposures to hospitalization. Those with direct exposure to hospitalization reported higher PTS. Indirect exposure of Covid-19 related news through electronic media was also significantly associated with higher PTS. Exposure through print media did not lead to significant difference in PTS, but those reading only magazines reported significantly higher PTG than not reading magazines. The findings are analyzed in the light of unfolding of events during the second wave of Covid-19 in India.